Uma aborgagem biogeográfica dos cetáceos da costa brasileira - Siciliano, Salvatore (2001)
Cetaceans habitats along the Brazilian coast are described according to environmental features in six different areas: Natal-Costinha (5-7ºS), Recife-Salvador (7-l0ºS), Abrolhos Banks (l 7º30'S-18º20'S), Campos Basin (22º-24ºS), Santos Basin (24º-26ºS) and Pelotas Basin (28º-30ºS). The cetacean community along the Brazilian coast is comprised of 40 species, belonging to seven families: Balaenidae (n=l species), Balaenopteridae (7), Physeteridae (3), Delphinidae (20), Ziphiidae (7), Phocoenidae (1) and Pontoporiidae (1). Campos and Santos Basins support the highest species richness (n=32 species), followed by Pelotas Basin (31 ), Recife-Salvador (23), Natal-Costinha (21) and Abrolhos Banks (10). The highest diversity of cetacean species in Campos and Santos Basin can be explained by the penetration of South Atlantic Central waters (ACAS) which causes enrichment of such environment. The occurrence of some species are well connected to these upwelling conditions such as the dolphins of the genus Delphinus, the Atlantic spotted dolphin (Stenella frontalis) and the killer whale (Orcinus orca) as well as whales (Bryde's, Balaenoptera edeni and dwarf minke whale B. acutorostrata). ln contrast, such species are lacking along the coastal waters of the northeastern coast, indicating the oligotrophic structure of these waters. The offshore community is represented by three species of the genus Stenella, pantropical spotted, S. attenuata, clymene, S. clymene and spinner, S. longirostris, the sperm whale, Physeter macrocephalus, and migratory species, the Antarctic minke whale (B. bonaerensis) and the sei whale (B. borealis). Three species are widely distributed along the coastal waters of the Brazilian coast: the tucuxi (Sotalia fluviatilis), the bottlenose (Túrsiops truncatus) and the humpback whale (Megaptera novaeangliae). As a result of intensive observation and collection effort it was found that the franciscana (Pontoporia blainvillei) presents a disjunct distribution along the southeastern coast. This causes special concern for management and conservation issues regarding the franciscana. The Brazilian coast hosts a highly rich cetacean community when compared to other tropical oceans. Conversely, the species composition is different among the study sites and between ocean basins. Further studies are needed to better understand the variation among species composition within tropical oceans.